2019
DOI: 10.1161/hypertensionaha.119.12707
|View full text |Cite
|
Sign up to set email alerts
|

Placental Syncytiotrophoblast-Derived Extracellular Vesicles Carry Active NEP (Neprilysin) and Are Increased in Preeclampsia

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 27 publications
3
75
0
2
Order By: Relevance
“…Relevant for hypertension, EVs released by placental syncytiotrophoblasts carry neprilysin, an enzyme from the family of membrane-bound metalloproteases. Neprilysin cleaves vasopeptides, thus contributing to the establishment of hypertension, a hallmark of PE [80]. Interestingly, the rate of early onset of PE in high risk women could be significantly reduced by aspirin and this effect was mediated by down-regulation of miR-155 transported by EVs [81,82].…”
Section: Preeclampsiamentioning
confidence: 99%
“…Relevant for hypertension, EVs released by placental syncytiotrophoblasts carry neprilysin, an enzyme from the family of membrane-bound metalloproteases. Neprilysin cleaves vasopeptides, thus contributing to the establishment of hypertension, a hallmark of PE [80]. Interestingly, the rate of early onset of PE in high risk women could be significantly reduced by aspirin and this effect was mediated by down-regulation of miR-155 transported by EVs [81,82].…”
Section: Preeclampsiamentioning
confidence: 99%
“…Neprilysin (NEP) is a membrane‐bound metalloprotease that could reduce the activation of peptides such as vasodilators, natriuretics and diuretics. A recent study suggests that active NEP is highly expressed in STBEVs of PE patients, which are likely to be associated with the pathogenesis of PE …”
Section: Evs In Complicated Pregnancymentioning
confidence: 99%
“…Neprilysin (NEP), a membrane‐bound metalloprotease, is highly expressed in STBEVs from the plasma of PE patients as detected by flow cytometry. Thus, the higher level of PLAP + NEP + EVs is suggested as a promising biomarker of PE . Son et al demonstrate that the expression level of podocyte‐specific protein nephrin is elevated in the urine of PE women and is correlated with proteinuria and diastolic blood pressure.…”
Section: Evs As Biomarkers For Pregnancy‐related Diseasesmentioning
confidence: 99%
“…Interestingly, miR-210, a hypoxia-induced miRNA, recruiting Hypoxia Inducible Factor 1 Subunit Alpha (HIF-1α) and participating to angiogenesis and cell migration processes, is carried by EVs derived from extravillous and villous trophoblasts. It has been demonstrated that miR-210 is one of the most highly expressed miRNAs in the placenta as well as in the maternal blood [52,59,60]. Syncytiotrophoblast-derived EVs, staining positive for PLAP, were analyzed for several tRNA species in normal pregnancies.…”
Section: Extracellular Vesicles As Biomarkersmentioning
confidence: 99%